Inhibition of Phosphoenolpyruvate Carboxylase by Malate - Wedding, Randolph T. (1990)
Malate has been noted to be a `mixed' inhibitor of phosphoenolpyruvate (PEP) carboxylase. The competitive portion of this inhibition appears to be fairly constant regardless of the condition of the enzyme being measured, but the noncompetitive (V-type) inhibition is subject to variation depending on the source of the enzyme, its storage condition, the presence or absence of various ligands, and differences in pH. In the case of the maize (Zea mays L.) phosphoenolpyruvate carboxylase (PEPC), the V-type inhibition by malate is much less pronounced at pH 8 than at pH 7. Examination of the response of the maize PEPC to PEP concentration reveals a pronounced cooperativity at pH 8 which is not present at pH 7, and which results in the disappearance of the V-type inhibition at pH 8. The ability of high concentrations of PEP to convert PEPC from a form readily inhibited by malate to one resistant to malate inhibition has been previously demonstrated and we attribute the cooperativity shown at pH 8 to this response to high levels of PEP. Support for this proposal is provided by studies of the enzyme at pH 7 and pH 8 run in 20% glycerol. In this case there was no V-type inhibition of PEPC at either pH. Treatment with 20% glycerol has been shown to result in the aggregation of maize PEPC.